Hierarchically 3D structured milled lamellar MoS2/nano-silicon@carbon hybrid with medium capacity and long cycling sustainability as anodes for lithium-ion batteries. Issue 9 (September 2019) - Zhang, Peng; Ru, Qiang; Yan, Honglin; Hou, Xianhua; Chen, Fuming; Hu, Shejun; Zhao, Lingzhi
Abstract: A hierarchically 3D structured milled lamellar MoS2 /nano-silicon@carbon hybrid with medium capacity and long-term lifespan is designed by a green and scalable approach using ball milling process and spray-drying/pyrolysis routes. The microspheres consist of low-content nano-silicon (20 wt%), milled lamellar MoS2 sheets and porous carbon skeletons. A mixture of silicon nanoparticles and MoS2 flakes serves as an inner core, while porous carbon pyrolyzed from petroleum pitch acts as a protective shell. The particular architecture affords robust mechanical support, abundant buffering space and enhanced electrical conductivity, thus effectively accommodating drastic volume variation during repetitive Li + intercalation/extraction. The Si/MoS2 @C hybrid delivers a high initial discharge specific capacity of 1257.8 mA h g −1 and exhibits a reversible capacity of 767.52 mA h g −1 at a current density 100 mA g -1 after 250 cycles. Most impressively, the electrode depicts a superior long-cycling durability with a discharge capacity of 537.6 mA h g −1 even after 1200 cycles at a current density of 500 mA g -1 . Meanwhile, the hybrid also shows excellent rate performance such as 388.1 mA h g −1 even at a large current density of 3000 mA g -1 .